PELUANG USAHA KECIL KULINER RUMAHAN MASYARAKAT PERUM KHARISMA KOKA DITENGAH PANDEMI COVID 19 - Erric Kondoy; Rahmania Rahman (Mandala, 2020)
AbstrakThe policy of staying at home due to the prevention of the spread of Covid 19 is the primary of economic problems in the poor society since they were laid off by the company where they worked in and therefore, they cannot fulfill their family needs anymore. This reality force them to find solution to fulfill their family needs in which almost all society get impact of this including the Kharisma Koka residential. It encourages the people there particularly the housewives to concern with culinary business at home by selling various foods such as typical food of North Sulawesi and even some kinds of food from outside the province. Thishome culinary is regarded as the excellent business opportunity in the Covid 19 pandemic. Key words: Kharisma Koka residential, home industry, culinary business.